The Role Of Financial Technology (Fintech) In Financial Performance As A Moderator And Improving Financial Inclusion In Indonesia - Paulus Tahu, Gregorius; Verawati, Yenny (SEAN Institute, 2024)
Financial Technology (Fintech) has become an important innovation in the global financial sector, including in Indonesia, with its crucial role in increasing financial inclusion and moderating overall financial performance. Through a literature review method, this study explores how fintech affects access to financial services for various segments of society, especially those that were previously inaccessible to the traditional financial system. Fintech brings solutions such as digital payments, online lending, and investment platforms that enable individuals to actively participate in the digital economy. Fintech offers solutions by facilitating easier and cheaper access to financial services, as well as improving financial literacy through innovative educational approaches. In addition, fintech also moderates financial performance by improving firms' operational efficiency, better risk management, and real-time data-driven decision-making. The study concludes that with the right support from the government, regulators, and industry players, fintech has great potential to continue expanding financial inclusion and improving overall financial sector performance in Indonesia.